2018
DOI: 10.1038/s41419-018-0297-3
|View full text |Cite
|
Sign up to set email alerts
|

Norisoboldine, a natural AhR agonist, promotes Treg differentiation and attenuates colitis via targeting glycolysis and subsequent NAD+/SIRT1/SUV39H1/H3K9me3 signaling pathway

Abstract: Norisoboldine (NOR), a natural aryl hydrocarbon receptor (AhR) agonist, has been demonstrated to attenuate ulcerative colitis (UC) and induce the generation of Treg cells. Under UC condition, hypoxia widely exists in colonic mucosa, and secondary changes of microRNAs (miRs) expressions and glycolysis contribute to Treg differentiation. At present, we worked for exploring the deep mechanisms for NOR-promoted Treg differentiation in hypoxia and its subsequent anti-UC action from the angle of AhR/miR or AhR/glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 51 publications
1
60
0
Order By: Relevance
“…274,275 Tong et al 276 suggested that norisoboldine induced the generation of intestinal Treg cells by the activation of AhR (aryl hydrocarbon receptor) as well as promoted Treg differentiation and then reduced the development of colitis by regulating AhR/ glycolysis axis and subsequent NAD + /SIRT1/SUV39H1/H3K9me3 signaling pathway. 277 Furthermore, norisoboldine reduced IL-1β production in LPS-stimulated RAW264.7 cells and decreased the serum level of IL-1β in collagen-induced arthritis. 272,278 Finally, the compound inhibited activation of the NLRP3 inflammasome by regulating the AhR/Nrf2/ ROS signaling pathway and thereby improved the TNBS (2,4,6-trinitrobenzene sulfonic acid)-induced colitis in mice.…”
Section: Anti-inflammatory and Immunosuppressive Activitiesmentioning
confidence: 94%
“…274,275 Tong et al 276 suggested that norisoboldine induced the generation of intestinal Treg cells by the activation of AhR (aryl hydrocarbon receptor) as well as promoted Treg differentiation and then reduced the development of colitis by regulating AhR/ glycolysis axis and subsequent NAD + /SIRT1/SUV39H1/H3K9me3 signaling pathway. 277 Furthermore, norisoboldine reduced IL-1β production in LPS-stimulated RAW264.7 cells and decreased the serum level of IL-1β in collagen-induced arthritis. 272,278 Finally, the compound inhibited activation of the NLRP3 inflammasome by regulating the AhR/Nrf2/ ROS signaling pathway and thereby improved the TNBS (2,4,6-trinitrobenzene sulfonic acid)-induced colitis in mice.…”
Section: Anti-inflammatory and Immunosuppressive Activitiesmentioning
confidence: 94%
“…The study further found a link between NOR and Nrf2, a nuclear transcriptional factor of Cap'n' Collar family that can inhibit NLRP3 priming [172], as the mechanism for NOR-induced inhibition of NLRP3 inflammasome activation; where NOR up-regulated the expression of Nrf2 but down-regulated the production of ROS signals in THP-1 cells [169]. Concurrently, Qi et al also demonstrated that NOR was able to produce anti-UC effects through the suppression of glycolysis and promotion of T reg cell differentiation in hypoxic microenvironments via regulation of the NAD + /SIRT1/SUV39H1/H3K9me3 signalling pathway [170].…”
Section: Therapeutic Potential Of Ahr As a Natural Nlrp3 Inflammasomementioning
confidence: 96%
“…NOR has been shown to be a natural AhR ligand by Qi et al through its up-regulation of CYP1A1 expression, promotion of AhR nuclear translocation after dissociation of the AhR/Hsp90 complex and transcriptional activity of AhR/ARNT via DNA binding to the XRE region in THP-1 cells [169]. Studies also reveal that NOR promotes T reg cell differentiation from naïve T-cells in-vitro and increased its immunosuppressive effects on T eff cells through inducing apoptotic events and inhibiting T h 1 and T h 17 differentiation [170,171]. In the context of IBD, NOR has also been demonstrated to reduce NLRP3, ASC and caspase-1 expression in TNBS-induced mice, which could imply that NOR has inhibitory effects on NLRP3 inflammasome activation through an AhR pathway [169].…”
Section: Therapeutic Potential Of Ahr As a Natural Nlrp3 Inflammasomementioning
confidence: 98%
See 1 more Smart Citation
“…Several mechanisms could explain such effect. Accordingly, Norisoboldine (NOR), an AhR agonist, has been demonstrated to enhance Treg polarization by elevating both protein and mRNA levels of Foxp3 in CD4 + T cells via a glycolysis dependent manner . Other AhR agonists such as 3,3'‐diindolylmethane (DIM) and indole‐3‐carbinol (I3C) were found to promote Treg differentiation by targeting some microRNAs (miR‐31, miR‐219, and miR‐490), which modulate Foxp3 gene expression …”
Section: Resultsmentioning
confidence: 99%